Approaches to context representation in chosen information technologies - Jakubczyc, Janina A.; Owoc, Mieczysław L. (Podejścia do reprezentacji kontekstu w wybranych technologiach informacyjnych, 2011)
Development of modern information technologies supporting business is strictly tied with assuring universal solutions used in different applications. One of the crucial factors in this area enabling the application of parameters in different situations is a context approach. The main goal of this paper is stressing the importance and selected solutions in respect of representation of contexts, taking into account several class applications representing different information technologies (databases, network systems and intelligent systems). Apart from discussion about the essence of representation of contexts (sorts of context and ways of its representation) the specialty of context usability in the mentioned areas is presented
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 202, s. 30-36
Keywords: context representation; information technologies; software applications